Familial aggregation of "apple peel" intestinal atresia and cardiac left‐sided obstructive lesions: A possible causal relationship with NOTCH1 gene mutations. Issue 8 (20th May 2019) - Digilio, M. Cristina; Magliozzi, Monia; Di Pede, Alessandra; Valfrè, Laura; Dentici, Maria Lisa; Auriti, Cinzia; Marino, Bruno; Novelli, Antonio; Dallapiccola, Bruno
Abstract: "Apple peel" intestinal atresia is a rare form of small bowel atresia, in which the duodenum or proximal jejunum ends in a blind pouch and the distal small bowel wraps around its vascular supply, in a spiral resembling an apple peel. The etiology of "apple peel" intestinal atresia is presently unknown, although a congenital or acquired intestinal vascular accident can have a role in the pathogenesis. We report a family in which the proband affected by "apple peel" intestinal atresia, had a sibling (an interrupted pregnancy), and a paternal cousin with cardiac left‐sided obstructive lesions. Molecular testing for NOTCH1 gene was carried out in the proband, because pathogenic mutations in this gene have been associated with familial and sporadic cardiac left‐sided obstructive lesions and vascular anomalies, both isolated or within the spectrum of the Adams‐Oliver syndrome (AOS). The heterozygous c.2734C>T (p.Arg912Trp) NOTCH1 variant was found in the proband with "apple peel" intestinal atresia and in his father. This result argues for a possible causal relationship between NOTCH1 gene mutations and some forms of intestinal defects, through a vascular mechanism. The spectrum of NOTCH1 ‐associated malformations is widened. Genetic counseling should take into account intrafamilial variable clinical expression and incomplete penetrance.